Avaliação da atividade antimicrobiana in vitro do extrato hidroalcoólico das folhas da Persea gratissima Gaertn - Abacateiro - (Lauraceae) - Reis, Marcos Osorio Rocca dos (2006)
This work aimed to evaluate the antimicrobial activity in vitro of the hydroalcoholic extract obtained through the leaves of Persea gratissima Gaertn - Avocado - (Lauraceae), and therefore, the extract was obtained by the maceration process, rotoevaporated and afterwards, its activity was verified. antimicrobial, against a panel of microorganisms, including Gram positive and negative bacteria and fungi (yeasts), using the Agar diffusion method, using the Disco techniques as described by Bauer et al. (1966) and the double layer well, described by Grove and Randall (1955). Knowing that the above techniques are qualitative, it was then decided to determine the Minimum Inhibitory Concentration, using the broth dilution technique (microtechnique) described by Andrews with adaptations. With the results obtained by the Agar Diffusion method, we can conclude that, although inhibition halos have been observed for some microorganisms by the disc technique, in the analysis of variance it was observed that only for K. rhizophila ATCC # 9341 there was a significant difference between the concentrations, the same occurring by the well technique, where K. rhizophila ATCC # 9341, P. aeruginosa ATCC # 27853 and K. pneumoniae c / c 46, showed significant differences between the concentrations. Comparing the results of the Well and Disc techniques, there was disagreement as to the results obtained for the tested microorganisms, however, doing the Analysis of Variances for the comparison between the two techniques only for the microorganisms S. aureus c / c and K. rhizophila ATCC # 9341, there was a significant difference. Knowing that the method of diffusion in Agar by the two techniques, Well and Disc, can suffer interference, and because these qualitative tests, the determination of the Minimum Inhibitory Concentration (MIC) was performed with the same extract and with the same organisms tested. where the results showed inhibition of bacterial growth with all inocula, showing to be more efficient for C. krusei ATCC 6258.